Design and Implementation of a Digital Marketing Technology Innovation Application (E-Commerce) in Coffee and Derivative Product Marketing to Increase the Income of Coffee Farmers and Entrepreneurs - Yulisda, Desvina; Razi, Ar; Muliana, Erna (Universitas Negeri Padang, 2025)
The most prominent coffee-producing regions in Indonesia are Central Aceh and Bener Meriah Regencies, situated within the Gayo Highlands. Presently, a considerable proportion of coffee farmers and local communities remain unaware of the potential value of high-value coffee derivatives. Furthermore, many lack the requisite skills to utilise technology, particularly in the context of agricultural technology innovations that could facilitate the marketing of coffee products and coffee-based derivatives. This agricultural technology innovation pertains to digital marketing, encompassing both desktop and mobile-based platforms, which collectively constitute e-commerce. Some studies have explored the theme of e-commerce for coffee products, but the products sold are predominantly limited to coffee beans and ground coffee. This suggests a dearth of knowledge and interest among farmers and communities in developing coffee-based innovations such as beauty products, food ingredients, coffee oil, coffee charcoal, and others. This research project aims to develop an e-commerce application for the marketing of agricultural products, to increase the knowledge and income of farmers and communities from coffee and its derivatives through the use of a mobile application, and to include expert consultation features in the aforementioned e-commerce application. The methodology employed in this research is a literature review and system development using the waterfall model, beginning with analysis and concluding with system maintenance. The result of this study is an e-commerce application for the marketing of coffee and its derivative products.